THE USE OF CLOVE OIL (Syzygium aromaticum) AS AN ANESTHETIC TO THE SURVIVAL RATE OF VANAME (Litopenaeus vannamei) POSTLARVAE IN TRANSPORTATION - Agung Doni Anggoro; Muhammad Rasnijal; Umidayati Umidayati; Dyah Retno Wulan; Yernawilis Yernawilis (Universitas Mataram, 2025)
This study employed a Completely Randomized Design (CRD) consisting of four treatments with three (3) replications, resulting in a total of twelve (12) experimental units: P1 0%, P2 0.10%, P3 0.20%, and P4 0.30%. The use of clove oil doses on shrimp seed survival during closed transportation showed significant differences among the treatment groups, where P < 0.05. Survival rates for each treatment were as follows: P1 at 53.1%, P2 at 87.9%, P3 at 88.7%, and P4 at 62.4%. Based on measurements of water quality parameters during the study, the conditions in the plastic bag containers after 24 hours of transportation remained within tolerance limits that support shrimp seed maintenance. The post-transport water quality values were: temperature 29.38–29.41°C, dissolved oxygen 4.70–4.75 ppm, and pH 7.30–7.39.